SiC / SiC composite material cladding tube as well as preparation method and application thereof

Through vacuum impregnation and chemical vapor-phase permeation processes, the tightness of SiC/SiC composite clad tubes is improved, and the problem of insufficient airtightness and thermal conductivity in the prior art is solved through multi-layer SiC coating deposition technology, and the problem of insufficient airtightness and thermal conductivity in the prior art has been achieved. Performance that meets application requirements in nuclear reactors.

CN119161199APending Publication Date: 2024-12-20STATE POWER INVESTMENT CORPORATION RESEARCH INSTITUTE
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310729688.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing SiC/SiC composite clad tube has a high porosity after CVI densification, and the brittle CVD-SiC coating is prone to cracks, affecting the airtightness and thermal conductivity, making it difficult to maintain good airtightness under 20MPa positive pressure conditions. and achieve thermal conductivity above 20W/m·k, limiting its application in nuclear reactors.

Method used

The densified SiC/SiC composite intermediate layer is obtained by vacuum impregnation, curing and cracking, and the SiC layer is deposited on its outer surface by chemical vapor permeation process to improve the interface between the coating and the intermediate layer, and then form multiple forms through chemical vapor deposition process SiC coating to enhance airtightness and thermal conductivity.

Benefits of technology

It achieves good airtightness without obvious leakage under 20MPa positive pressure conditions and thermal conductivity higher than 20W/m·k, which meets the application requirements of the reactor, and only contains silicon carbide components, avoiding binding strength and thermal chemical phases. Capacity issues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161199A_ABST
    Figure CN119161199A_ABST
Patent Text Reader

Abstract

The invention discloses a SiC / SiC composite material cladding tube and a preparation method and application thereof, and the preparation method comprises the following steps: carrying out vacuum impregnation on a SiC / SiC composite material tube in a SiC precursor solution, and after vacuum impregnation, carrying out curing and cracking to obtain a densified SiC / SiC composite material middle layer; depositing a SiC layer on the outer surface of the SiC / SiC composite material middle layer by adopting a chemical vapor infiltration process; and depositing the SiC layer on the surface of the SiC layer obtained by deposition by adopting a chemical vapor deposition process. According to the method, through densification improvement of the SiC / SiC composite material middle layer and improvement of the outer coating process, the air tightness and the heat conductivity of the SiC / SiC composite material cladding tube are remarkably improved, the good air tightness without obvious leakage under the positive pressure condition of 20 MPa is achieved, the heat conductivity higher than 20 W / m.k is achieved, and the application requirement of a reactor is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of nuclear engineering, and in particular to a SiC / SiC composite cladding tube and a preparation method and application thereof. Background Art

[0002] Silicon carbide (SiC) is an ideal cladding tube material due to its high temperature resistance, corrosion resistance, oxidation resistance and small neutron absorption cross section. The SiC composite material (SiC / SiC) cladding tube toughened with continuous SiC fibers can overcome the brittleness of single ceramics, significantly improve mechanical properties, and improve the safety of the reactor from the source.

[0003] SiC / SiC composite cladding tubes are usually multi-layer structures, including a SiC / SiC composite intermediate layer and a single-element SiC ceramic coating. The SiC / SiC composite intermediate layer is the main load-bearing unit of the cladding tube. Usually, the fibers are first woven to obtain a fiber preform, and then densified to obtain a high-purity SiC / SiC composite intermediate layer; the coating is a single-element SiC ceramic layer, which can prevent fission gas leakage and enhance environmental corrosion resistance.

[0004] The performance of SiC / SiC composite cladding tubes depends largely on the process route adopted. The middle layer of SiC / SiC composite materials is usually further densified on the basis of fiber weaving or winding. Densification processes include chemical vapor infiltration (CVI), nanopowder infiltration and instant eutectic phase method (NITE) and polymer infiltration and pyrolysis technology (PIP). Among them, CVI technology is widely used because of its high crystallinity, purity, stoichiometric ratio, the preparation process does not affect the fiber strength and can be applied to the preparation of large and complex materials. However, the final porosity of the SiC matrix prepared by CVI technology is usually 10%-20%, which is inevitable when using CVI technology alone. The airtightness and thermal conductivity of the prepared cladding tube are difficult to meet the requirements, which limits the application of SiC / SiC composite materials in reactors.

[0005] The single-element SiC ceramic layer is usually prepared by chemical vapor deposition (CVD). The difficulty in the preparation process of the coating single-element SiC ceramic layer is to prepare a SiC ceramic layer of a certain thickness to meet the requirements of air tightness and good bonding with the composite material intermediate layer.

[0006] Therefore, in nuclear reactor applications, how to further improve the density of the intermediate layer and improve the coating quality to meet the requirements of air tightness and thermal conductivity has become a key link affecting the application prospects of SiC / SiC composite cladding tubes. Summary of the invention

[0007] The present invention is based on the inventor's discovery and understanding of the following facts and problems: According to the current research status at home and abroad, the current SiC / SiC composite cladding tube preparation process still has deficiencies, such as the high porosity of the middle layer of the SiC / SiC composite material after CVI densification, and the brittle CVD-SiC coating is prone to cracks under stress, volume change, etc., affecting the airtightness of the cladding tube; the porosity of the SiC / SiC composite material, the crystallinity of the SiC matrix and the coating, and the interface between the coating and the SiC / SiC composite material layer will affect the thermal conductivity of the cladding tube. At present, there is no SiC / SiC composite cladding tube preparation process that can enable the SiC / SiC composite cladding tube to achieve good airtightness without obvious leakage under 20MPa positive pressure conditions, and achieve a thermal conductivity higher than 20W / m·k, which limits the application of SiC / SiC composite materials in reactors.

[0008] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the embodiments of the present invention provide a SiC / SiC composite cladding tube and a preparation method and application thereof, which significantly improves the air tightness and thermal conductivity of the SiC / SiC composite cladding tube by improving the densification of the intermediate layer of the SiC / SiC composite material and improving the outer coating process, and can achieve good air tightness without obvious leakage under 20MPa positive pressure conditions, and can also achieve a thermal conductivity higher than 20W / m·k, meeting the application requirements of the reactor.

[0009] The embodiment of the present invention provides a method for preparing a SiC / SiC composite cladding tube, comprising the following steps:

[0010] (1) vacuum impregnating a SiC / SiC composite material tube in a SiC precursor solution, and after vacuum impregnation, curing and cracking are performed to obtain a densified SiC / SiC composite material intermediate layer;

[0011] (2) depositing a SiC layer on the outer surface of the densified SiC / SiC composite material intermediate layer obtained in step (1) by a chemical vapor infiltration process;

[0012] (3) Depositing a SiC layer on the surface of the SiC layer deposited in step (2) using a chemical vapor deposition process.

[0013] The advantages and technical effects brought by the preparation method of the SiC / SiC composite cladding tube of the embodiment of the present invention are as follows: the SiC / SiC composite tube is vacuum impregnated, solidified, and cracked in a SiC precursor solution to further densify the SiC / SiC composite tube to obtain a densified SiC / SiC composite intermediate layer; then a SiC layer is deposited on the outer surface of the SiC / SiC composite intermediate layer by a chemical vapor infiltration process to densify the SiC / SiC composite tube and improve the interface between the SiC coating and the composite intermediate layer; a SiC layer is deposited on the surface of the SiC layer obtained by chemical vapor infiltration deposition by a chemical vapor deposition process. By improving the densification of the SiC / SiC composite intermediate layer and improving the outer coating process, the air tightness and thermal conductivity of the SiC / SiC composite cladding tube are significantly improved, which can achieve good air tightness without obvious leakage under 20MPa positive pressure conditions, and can also achieve a thermal conductivity higher than 20W / m·k, meeting the application requirements of the reactor.

[0014] In the embodiment of the present invention, without introducing other components except SiC, the SiC / SiC composite material tube that has completed SiC fiber weaving and preliminary SiC matrix deposition can be further processed to obtain a SiC / SiC composite material cladding tube whose air tightness and thermal conductivity meet the reactor application requirements. The prepared cladding tube contains only silicon carbide components and does not contain other material components. It will not have problems such as bonding strength, thermochemical compatibility, and expansion coefficient mismatch, and retains the good performance of silicon carbide itself.

[0015] In some embodiments, in step (3), the process of depositing the SiC layer by the chemical vapor deposition process includes at least two chemical vapor deposition stages;

[0016] And / or, the chemical vapor deposition process of depositing the SiC layer is uninterrupted.

[0017] In some embodiments, in step (3), the process of depositing the SiC layer by the chemical vapor deposition process includes 2-6 chemical vapor deposition stages.

[0018] In some embodiments, in the step (3), the deposition temperature of the first chemical vapor deposition stage of the chemical vapor deposition process for depositing the SiC layer is 1100-1400° C.;

[0019] and / or, the deposition temperature of each chemical vapor deposition stage is 50 to 150° C. lower than the deposition temperature of the previous chemical vapor deposition stage;

[0020] And / or, the deposition time of each chemical vapor deposition stage is 5 to 20 hours.

[0021] In some embodiments, in step (3), hydrogen, argon and trichloromethylsilane are introduced into the chemical vapor deposition process; the molar ratio of the hydrogen to trichloromethylsilane is 8 to 12:1;

[0022] And / or, the pressure of the chemical vapor deposition is 15-25 kPa.

[0023] In some embodiments, in step (1), the preparation of the SiC / SiC composite material tube comprises: weaving SiC fibers into a SiC fiber preform, and then preparing the SiC fiber preform through a SiC matrix to obtain a SiC / SiC composite material tube; the preparation method of the SiC matrix comprises at least one of chemical vapor infiltration, chemical vapor deposition, precursor impregnation pyrolysis, and nano-impregnation transient eutectic;

[0024] And / or, the SiC precursor solution includes a polymer precursor and a solvent; the polymer precursor includes at least one of polycarbosilane, polymethylsilane, and polyvinylsilane; the solvent includes at least one of xylene, toluene, and trimethylbenzene;

[0025] And / or, the room temperature viscosity of the SiC precursor solution is 20 to 40 mPa·s;

[0026] and / or, the vacuum impregnation pressure is less than 5×10 -3 Pa; the vacuum impregnation time is 2 to 15 hours;

[0027] And / or, the cracking temperature is 1000-1300° C.; the cracking time is 0.5-2 h.

[0028] In some embodiments, in the step (1), the vacuum impregnation, curing and cracking process in step (1) is repeated; the vacuum impregnation, curing and cracking process is repeated 2 to 10 times until the surface fibers of the SiC / SiC composite material tube are completely covered by the SiC matrix obtained by impregnation and cracking of the SiC precursor solution, and the mass increase rate of the SiC is less than 1%, and the vacuum impregnation, curing and cracking process is stopped to obtain a densified SiC / SiC composite material intermediate layer.

[0029] In some embodiments, in step (2), hydrogen, argon and trichloromethylsilane are introduced into the chemical vapor infiltration process, and the molar ratio of hydrogen to trichloromethylsilane is 8 to 12:1;

[0030] And / or, the deposition temperature is 900-1200° C.; the deposition pressure is 2-6 kPa; the deposition time is 2-8 h;

[0031] And / or, after the SiC layer is deposited by chemical vapor infiltration process, the introduction of trichloromethylsilane is stopped, and then the temperature is kept at 900-1200° C. for 0.5-3 hours.

[0032] The SiC / SiC composite cladding tube of the embodiment of the present invention is prepared by the preparation method of the embodiment of the present invention. In the embodiment of the present invention, the SiC / SiC composite cladding tube can achieve good air tightness without obvious leakage under 20MPa positive pressure conditions, and can also achieve a thermal conductivity higher than 20W / m·k, meeting the application requirements of the reactor.

[0033] The SiC / SiC composite cladding tube prepared by the preparation method of the embodiment of the present invention or the application of the SiC / SiC composite cladding tube of the embodiment of the present invention, the SiC / SiC composite cladding tube is used in a nuclear reactor. In the embodiment of the present invention, the SiC / SiC composite cladding tube can achieve good airtightness without obvious leakage under 20MPa positive pressure conditions, and can also achieve a thermal conductivity higher than 20W / m·k, meeting the application requirements of the reactor, especially being able to meet the airtightness and thermal conductivity requirements of the pressurized water reactor service environment, and can not only be used in the service environment of the pressurized water reactor, but also has good application prospects in various reactors such as the fourth-generation high-temperature reactor, high-power nuclear reactor, and full-life small reactor. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 : (a) SEM image of the original SiC / SiC composite material tube in Example 1 of the present invention; (b) SEM image of the prepared SiC / SiC composite material cladding tube.

[0035] Figure 2 This is the internal pressure curve of the SiC / SiC composite cladding tube in Example 1 of the present invention maintained at an internal pressure of 15 MPa for 72 hours.

[0036] Figure 3 It is the SiC outer coating of the SiC / SiC composite cladding tube in Example 1 of the present invention.

[0037] Figure 4 (a) The morphology of the SiC outer coating of the SiC / SiC composite cladding tube in Comparative Example 1; (b) The pyrolytic carbon interface layer between the SiC outer coating and the composite material.

[0038] Figure 5 (a) The morphology of the SiC outer coating of the SiC / SiC composite cladding tube in Comparative Example 2; (b) The interface between the SiC outer coating and the composite material. DETAILED DESCRIPTION

[0039] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0040] The method for preparing the SiC / SiC composite cladding tube according to the embodiment of the present invention comprises the following steps:

[0041] (1) vacuum impregnating a SiC / SiC composite material tube in a SiC precursor solution, and after vacuum impregnation, curing and cracking are performed to obtain a densified SiC / SiC composite material intermediate layer;

[0042] (2) depositing a SiC layer on the outer surface of the densified SiC / SiC composite material intermediate layer obtained in step (1) by a chemical vapor infiltration process;

[0043] (3) Depositing a SiC layer on the surface of the SiC layer deposited in step (2) using a chemical vapor deposition process.

[0044] The preparation method of the SiC / SiC composite cladding tube of the embodiment of the present invention is to vacuum impregnate, solidify and crack the SiC / SiC composite tube in a mixed solution of SiC precursors, further densify the SiC / SiC composite tube, and obtain a densified SiC / SiC composite intermediate layer; then deposit a SiC layer on the outer surface of the SiC / SiC composite intermediate layer by chemical vapor infiltration process to densify the SiC / SiC composite tube and improve the interface between the SiC coating and the composite intermediate layer; and deposit a SiC layer on the surface of the SiC layer obtained by chemical vapor infiltration deposition by chemical vapor deposition process. By improving the densification of the SiC / SiC composite intermediate layer and improving the outer coating process, the air tightness and thermal conductivity of the SiC / SiC composite cladding tube are significantly improved, which can achieve good air tightness without obvious leakage under 20MPa positive pressure conditions, and can also achieve a thermal conductivity higher than 20W / m·k, meeting the application requirements of the reactor.

[0045] In the embodiment of the present invention, without introducing other components except SiC, the SiC / SiC composite material tube that has completed SiC fiber weaving and preliminary SiC matrix deposition can be further processed to obtain a SiC / SiC composite material cladding tube whose air tightness and thermal conductivity meet the reactor application requirements. The prepared cladding tube contains only silicon carbide components and does not contain other material components. It will not have problems such as bonding strength, thermochemical compatibility, and expansion coefficient mismatch, and retains the good performance of silicon carbide itself.

[0046] In some embodiments, in step (3), the process of depositing the SiC layer by the chemical vapor deposition process includes at least two chemical vapor deposition stages; and / or, the deposition process of the SiC layer by the chemical vapor deposition process is uninterrupted. In the embodiment of the present invention, more than two chemical vapor deposition stages are included, which can form a CVD coating of more than two layers of SiC, and can avoid the formation of through cracks in the coating, which is beneficial to further improve the air tightness and thermal conductivity; the deposition of the SiC layer during the chemical vapor deposition process is continuous and uninterrupted, and there is no obvious interface between the coatings obtained by the two CVDs, which can avoid the reduction of interlayer bonding strength and interlayer thermal conductivity, and is beneficial to further improve the air tightness and thermal conductivity.

[0047] In some embodiments, in step (3), the process of depositing the SiC layer by the chemical vapor deposition process includes 2-6 chemical vapor deposition stages, specifically, for example, 2, 3, 4, 5, 6. In the embodiment of the present invention, by optimizing the number of stages of the chemical vapor deposition process, it is beneficial to further improve the air tightness and thermal conductivity.

[0048] In some embodiments, the deposition temperature of each chemical vapor deposition stage is 50-150° C. lower than the deposition temperature of the previous chemical vapor deposition stage, specifically, for example, 50° C., 75° C., 100° C., 125° C., 150° C. In the embodiments of the present invention, by preferably decreasing the deposition temperature of each chemical vapor deposition stage by 50-150° C., the coating layer can be effectively generated, and the layers are tightly bonded, which is beneficial to further improve the air tightness and thermal conductivity.

[0049] In some embodiments, in step (3), the deposition temperature of the first chemical vapor deposition stage of the chemical vapor deposition process of depositing the SiC layer is 1100-1400°C, specifically, for example, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C; and / or, the deposition time of each chemical vapor deposition stage is 5-20h, specifically, for example, 5h, 8h, 10h, 12h, 15h, 18h, 20h. In the embodiment of the present invention, by preferably setting the deposition time of each chemical vapor deposition stage to 5-20h, the deposition time is short, which is conducive to shortening the preparation cycle and improving production efficiency. By optimizing the temperature and time of the chemical vapor deposition process, it is conducive to further improving air tightness and thermal conductivity.

[0050] In some embodiments, in step (3), hydrogen, argon and trichloromethylsilane are introduced into the chemical vapor deposition process; the molar ratio of the hydrogen to trichloromethylsilane is 8 to 12:1, specifically, for example, 8:1, 9:1, 10:1, 11:1, 12:1;

[0051] In a specific embodiment, optionally, the flow rate of the hydrogen is 1L / min to 5L / min, specifically, for example, 1L / min, 2L / min, 3L / min, 4L / min, 5L / min; the flow rate of the argon is 2L / min to 10L / min, specifically, for example, 2L / min, 4L / min, 5L / min, 6L / min, 8L / min, 10L / min;

[0052] And / or, the pressure of the chemical vapor deposition is 15-25 kPa, specifically, for example, 15 kPa, 18 kPa, 20 kPa, 22 kPa, 25 kPa.

[0053] In some embodiments, in step (3), after the deposition is completed, the gas is stopped and the temperature in the furnace is reduced to room temperature; the average cooling rate is 15 to 25°C / h, specifically, for example, 15°C / h, 20°C / h, 25°C / h.

[0054] In some embodiments, in step (3), after the chemical vapor deposition process is completed, the surface of the material is polished to remove surface particles and protrusions to make the surface smooth, and to remove dust remaining on the surface during the polishing process.

[0055] In some embodiments, in step (1), the preparation of the SiC / SiC composite material tube includes: weaving SiC fibers into a SiC fiber preform, and then preparing the SiC fiber preform through a SiC matrix to obtain a SiC / SiC composite material tube; the preparation method of the SiC matrix includes at least one of chemical vapor infiltration, chemical vapor deposition, precursor impregnation pyrolysis, and nano-impregnation transient eutectic. In an embodiment of the present invention, SiC fibers are woven into a SiC fiber preform, and then a SiC matrix is ​​prepared to obtain a SiC / SiC composite material tube.

[0056] In some embodiments, in step (1), the SiC precursor solution includes a polymer precursor and a solvent; the polymer precursor includes at least one of polycarbosilane, polymethylsilane, and polyvinylsilane; the solvent includes at least one of xylene, toluene, and trimethylbenzene;

[0057] and / or, the room temperature viscosity of the SiC precursor solution is 20 to 40 mPa·s, specifically, for example, 20 mPa·s, 25 mPa·s, 30 mPa·s, 35 mPa·s, 40 mPa·s;

[0058] and / or, the vacuum impregnation pressure is less than 5×10 -3 Pa, specifically, for example, 4×10 -3 Pa, 3×10 -3 Pa, 2×10-3 The vacuum impregnation time is 2 to 15 hours, specifically, for example, 2 hours, 3 hours, 4 hours, 5 hours, 8 hours, 10 hours, 15 hours. In the embodiment of the present invention, the parameters of the vacuum impregnation process are optimized to further improve the air tightness and thermal conductivity.

[0059] In some embodiments, in step (1), the curing includes drying the SiC / SiC composite material tube after vacuum impregnation.

[0060] In some embodiments, in the step (1), the vacuum impregnated SiC / SiC composite material tube is dried at 1000-1200°C, specifically, for example, 1000°C, 1100°C, 1200°C; the drying time is 0.5-2h, specifically, for example, 0.5h, 1h, 1.5h, 2h. In the embodiment of the present invention, the drying can solidify the impregnated precursor, which is beneficial to the densification of the SiC matrix.

[0061] In some embodiments, in step (1), the pyrolysis is performed in an argon atmosphere; the pyrolysis temperature is 1000-1300°C, specifically, for example, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C; the pyrolysis time is 0.5-2h, specifically, for example, 0.5h, 1h, 1.5h, 2h; and the temperature is slowly reduced to room temperature after the pyrolysis is completed. In the embodiment of the present invention, by optimizing the parameters of the pyrolysis process, the precursor solution immersed in the SiC / SiC composite material tube is converted into a SiC ceramic matrix, which is beneficial to further improve the air tightness and thermal conductivity.

[0062] In some embodiments, in the step (1), the process of vacuum impregnation, curing and cracking in step (1) is repeated; the process of vacuum impregnation, curing and cracking is repeated 2 to 10 times, specifically, for example, 2, 3, 4, 5, 6, 7, 8, 9, 10, until the surface fibers of the SiC / SiC composite material tube are completely covered by the SiC matrix obtained by impregnation and cracking of the SiC precursor solution, and the mass increase rate of SiC is less than 1%, and the process of vacuum impregnation, curing and cracking is stopped to obtain a densified SiC / SiC composite material intermediate layer. In the embodiment of the present invention, repeating the process of vacuum impregnation-curing-cracking can further improve the compactness of the composite material intermediate layer, which is conducive to further improving the air tightness and thermal conductivity of the SiC / SiC composite material cladding tube.

[0063] In some embodiments, in step (1), the vacuum impregnation is to place the SiC / SiC composite material tube in a 316L stainless steel tube for vacuum impregnation, the tube diameter is 10 cm, and ventilation pipes are provided at both ends of the stainless steel tube for injecting SiC precursor solution and evacuating the vacuum.

[0064] In some embodiments, in step (1), argon gas is introduced to allow the SiC precursor solution to flow out, and argon gas is continuously introduced to dry the SiC / SiC composite material tube after vacuum impregnation. In the embodiments of the present invention, the drying can solidify the impregnated precursor, which is beneficial to the densification of the SiC matrix.

[0065] In some embodiments, in step (1), after the cracking treatment, the surface of the SiC / SiC composite material tube is polished to remove surface particles and protrusions to make the surface smooth, and dust remaining on the surface during the polishing process is removed.

[0066] In some embodiments, in step (2), hydrogen, argon and trichloromethylsilane are introduced into the chemical vapor infiltration process, and the molar ratio of the hydrogen to trichloromethylsilane is 8 to 12:1, specifically, for example, 8:1, 9:1, 10:1, 11:1, 12:1;

[0067] In a specific embodiment, optionally, the flow rate of the hydrogen is 1L / min to 5L / min, specifically, for example, 1L / min, 2L / min, 3L / min, 4L / min, 5L / min; the flow rate of the argon is 2L / min to 10L / min, specifically, for example, 2L / min, 4L / min, 5L / min, 6L / min, 8L / min, 10L / min;

[0068] And / or, the deposition temperature is 900-1200°C, specifically, for example, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C; the deposition pressure is 2-6kPa, specifically, for example, 2kPa, 3kPa, 4kPa, 5kPa, 6kPa, and the deposition time is 2-8h, specifically, for example, 2h, 4h, 6h, 8h;

[0069] And / or, after the SiC layer is deposited by the chemical vapor infiltration process, the introduction of trichloromethylsilane is stopped, and then the temperature is kept at 900-1200°C, specifically, for example, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C for 0.5-3 hours, specifically, for example, 0.5h, 1h, 2h, 3h; after the introduction of trichloromethylsilane gas is stopped, the flow rate of hydrogen and argon is gradually reduced, and the introduction of hydrogen and argon is completely stopped within 2-5 minutes.

[0070] In the embodiment of the present invention, hydrogen serves as a carrier gas, argon serves as a diluent gas, and trichloromethylsilane serves as a reaction gas. If the CVI deposition time is too long, the process efficiency will be reduced; if the deposition time is too short, it will not be conducive to the formation of a complete and uniform CVI layer. After the chemical vapor infiltration process is completed, heat preservation is beneficial to enhancing the stability of the CVI layer. By optimizing the parameters of the CVI process, a CVI layer can be obtained and the interface between the CVI layer and the composite material substrate can be improved, and the interface between the subsequent coating and the CVI layer can be improved, which is beneficial to further improve the air tightness and thermal conductivity of the SiC / SiC composite material cladding tube.

[0071] The SiC / SiC composite cladding tube of the embodiment of the present invention is prepared by the preparation method of the embodiment of the present invention. In the embodiment of the present invention, the SiC / SiC composite cladding tube can achieve good air tightness without obvious leakage under 20MPa positive pressure conditions, and can also achieve a thermal conductivity higher than 20W / m·k, meeting the application requirements of the reactor.

[0072] The SiC / SiC composite cladding tube prepared by the preparation method of the embodiment of the present invention or the application of the SiC / SiC composite cladding tube of the embodiment of the present invention, the SiC / SiC composite cladding tube is used in a nuclear reactor. In the embodiment of the present invention, the SiC / SiC composite cladding tube can achieve good airtightness without obvious leakage under 20MPa positive pressure conditions, and can also achieve a thermal conductivity higher than 20W / m·k, meeting the application requirements of the reactor, especially being able to meet the airtightness and thermal conductivity requirements of the pressurized water reactor service environment, and can not only be used in the service environment of the pressurized water reactor, but also has good application prospects in various reactors such as the fourth-generation high-temperature reactor, high-power nuclear reactor, and full-life small reactor.

[0073] In some embodiments, the reactor is a pressurized water reactor, a high temperature gas-cooled reactor, a lead-cooled fast reactor, a sodium-cooled fast reactor, or a molten salt reactor.

[0074] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0075] Example 1

[0076] A method for preparing a SiC / SiC composite cladding tube comprises the following steps:

[0077] (1) Precursor polycarbosilane (PCS) is dissolved in xylene to prepare a precursor solution, wherein the room temperature viscosity of the SiC precursor solution is 30 mPa·s.

[0078] (2) The SiC / SiC composite material tube is placed in a 316L stainless steel tube for vacuum impregnation, with a tube diameter of 10 cm. Ventilation pipes are provided near both ends of the stainless steel tube for injecting the precursor solution of the impregnated SiC and for vacuuming.

[0079] (3) The SiC precursor solution was injected into the stainless steel pipe through the ventilation pipe, and the SiC precursor solution was completely immersed in the SiC / SiC composite material tube. The ventilation ports at both ends and one end of the stainless steel pipe were sealed to keep it airtight. A mechanical pump and a molecular pump were used to evacuate the other end to make the air pressure in the stainless steel pipe lower than 2×10 -3 Pa, the SiC / SiC composite tube was vacuum impregnated for 3 hours.

[0080] (4) Argon gas was introduced into the stainless steel pipe to make the SiC precursor solution flow out, and argon gas was continuously introduced into the stainless steel pipe to dry the impregnated SiC / SiC composite material tube. The drying temperature was 1100° C. and the drying time was 1 hour.

[0081] (5) The dried SiC / SiC composite tube is taken out from the stainless steel pipe, placed in a high-temperature cracking furnace, and heated in an argon inert atmosphere at 1200° C. to convert the SiC precursor solution impregnated in the SiC / SiC composite tube into a SiC ceramic matrix. The high-temperature cracking is performed for 1 hour, and the temperature is slowly cooled to room temperature after the high-temperature cracking is completed.

[0082] (6) The SiC / SiC composite material tube is taken out of the high-temperature cracking furnace, and the surface of the SiC / SiC composite material tube is lightly polished to remove surface particles and protrusions to make the surface flat, and the dust remaining on the surface during the polishing process is removed.

[0083] (7) Repeat the vacuum impregnation-curing-cracking process of steps (2) to (6), and perform a total of 4 rounds of vacuum impregnation-curing-cracking process, the fibers on the surface of the SiC / SiC composite tube are completely covered, and the mass increase rate of the last round of PIP is less than 1%, thereby obtaining a densified SiC / SiC composite intermediate layer.

[0084] (8) The prepared densified SiC / SiC composite material intermediate layer was placed upright in a chemical vapor deposition furnace at 1000°C for chemical vapor infiltration (CVI). The specific process was as follows: hydrogen, argon and trichloromethylsilane were introduced into the furnace, wherein hydrogen served as a carrier gas with a flow rate of 3 L / min, argon served as a dilution gas with a flow rate of 6 L / min, and trichloromethylsilane served as a reaction gas, which was introduced into the reaction furnace by bubbling hydrogen in a trichloromethylsilane precursor solution; deposition was carried out at 1000°C, the reaction pressure in the furnace was controlled at 4 kPa, the molar ratio of hydrogen to trichloromethylsilane was 10:1, and the deposition time was 6 hours.

[0085] (9) The introduction of trichloromethylsilane gas was stopped, and then the flow rates of hydrogen and argon were gradually reduced and completely stopped within 5 minutes. The SiC / SiC composite material after the SiC layer was deposited was kept at 1000° C. in a furnace for 1 hour.

[0086] (10) The temperature of the deposition furnace was raised to 1250°C, and hydrogen, argon and trichloromethylsilane were introduced into the furnace again. The hydrogen flow rate was 3 L / min, and the argon flow rate was 6 L / min. Trichloromethylsilane was introduced into the reaction furnace by bubbling hydrogen in the precursor solution. The molar ratio of hydrogen to trichloromethylsilane was 10:1. The reaction pressure in the furnace was controlled to be 20 kPa. The first CVD stage was carried out, and the deposition time was 15 hours.

[0087] (11) The temperature was adjusted to 1150°C, and hydrogen, argon, and trichloromethylsilane were continuously introduced into the furnace. The hydrogen flow rate was 3 L / min, and the argon flow rate was 6 L / min. The molar ratio of hydrogen to trichloromethylsilane was 10:1. The reaction pressure in the furnace was controlled to be 20 kPa, and the second CVD stage was carried out. The deposition time was 10 hours.

[0088] (12) After the deposition is completed, the gas is stopped and the temperature in the furnace is lowered. The average cooling rate is 20°C / h. After the temperature in the furnace drops to room temperature, the sample that has completed CVD is taken out and the surface of the material is lightly polished to remove surface particles and protrusions to make the surface as smooth as possible. The dust remaining on the surface during the polishing process is removed to obtain a SiC / SiC composite cladding tube.

[0089] like Figure 1 and 3 As shown, the composite middle layer of the SiC / SiC composite cladding tube has achieved significant densification, and a SiC coating of hundreds of microns has been formed on the outer layer. There is no obvious interface layer between the coating and the composite middle layer, and there is no interface layer between the coatings deposited at two different temperatures.

[0090] The SiC / SiC composite cladding tube of Example 1 is densified by vacuum impregnation-curing-cracking process, and the CVI layer is formed by chemical vapor infiltration process, which improves the densification and improves the interface between the CVI layer and the composite matrix, and improves the interface between the subsequent CVD coating and the CVI layer. The double-layer CVD coating is deposited at a decreasing temperature to improve the air tightness and thermal conductivity. Figure 3 As shown, a double-layer CVD deposition is performed continuously with a decreasing deposition temperature to obtain a SiC outer coating with a thickness of about 330 microns. There is no obvious interface between the coatings obtained by the two CVD processes. The inner layer is about 150 microns thick and the outer layer is about 180 microns thick.

[0091] like Figure 2 As shown in Table 1, the overall helium leakage rate of the SiC / SiC composite cladding tube under 15MPa positive pressure is less than 10 -9 Pa·m 3 / s, and the pressure did not drop significantly during the 72-hour pressure maintenance; and no obvious leakage occurred under the 20MPa positive pressure condition for 72 hours.

[0092] As shown in Table 1, the thermal conductivity of the SiC / SiC composite cladding tube is higher than 20 W / m·k. The thermal conductivities of four parallel samples of the same batch of SiC / SiC composite cladding tubes are 20.31, 20.29, 22.64, and 21.69 W / m·k, respectively, and the average thermal conductivity is 21.23 W / m·k.

[0093] Example 2

[0094] A method for preparing a SiC / SiC composite cladding tube comprises the following steps:

[0095] (1) Precursor polycarbosilane (PCS) is dissolved in toluene to prepare a precursor solution, wherein the room temperature viscosity of the SiC precursor solution is 20 mPa·s.

[0096] (2) The SiC / SiC composite tube is placed in a 316L stainless steel tube for vacuum impregnation with a diameter of 10 cm. Ventilation pipes are provided near both ends of the stainless steel tube for injecting the precursor solution of the impregnated SiC and for vacuuming.

[0097] (3) The SiC precursor solution was injected into the stainless steel pipe through the ventilation pipe, and the SiC precursor solution was completely immersed in the SiC / SiC composite material tube. The ventilation pipe openings at both ends and one end of the stainless steel pipe were sealed to keep it airtight. A mechanical pump and a molecular pump were used to evacuate the other end to make the air pressure in the stainless steel pipe lower than 3×10 -3 Pa, the SiC / SiC composite tube was vacuum impregnated for 2 hours.

[0098] (4) Argon gas was introduced into the stainless steel pipe to allow the SiC precursor solution to flow out, and argon gas was continuously introduced into the stainless steel pipe to dry the impregnated SiC / SiC composite material tube. The drying temperature was 1100° C. and the drying time was 2 hours.

[0099] (5) The dried SiC / SiC composite material tube is taken out from the stainless steel pipe, placed in a high-temperature cracking furnace, and heated in an argon inert atmosphere at 1000° C. to convert the SiC precursor mixed solution immersed in the SiC / SiC composite material tube into a SiC ceramic matrix. The high-temperature cracking time is 2 hours, and the temperature is slowly cooled to room temperature after the high-temperature cracking is completed.

[0100] (6) The SiC / SiC composite material tube is taken out of the high-temperature cracking furnace, and the surface of the SiC / SiC composite material tube is lightly polished to remove surface particles and protrusions to make the surface flat, and the dust remaining on the surface during the polishing process is removed.

[0101] (7) Repeat the vacuum impregnation-curing-cracking process of steps (2) to (6), and perform the vacuum impregnation-curing-cracking process for a total of 6 rounds until the fibers on the surface of the SiC / SiC composite tube are completely covered, and the mass increase rate of the last round of PIP is less than 1%, thereby obtaining a densified SiC / SiC composite intermediate layer.

[0102] (8) The prepared densified SiC / SiC composite material intermediate layer is placed upright in a chemical vapor deposition furnace at 1200°C for chemical vapor infiltration (CVI). The specific process is as follows: hydrogen, argon and trichloromethylsilane are introduced into the furnace, wherein hydrogen serves as a carrier gas with a flow rate of 5 L / min, argon serves as a dilution gas with a flow rate of 10 L / min, and trichloromethylsilane serves as a reaction gas, which is introduced into the reaction furnace by bubbling hydrogen in a precursor solution; deposition is carried out at 1200°C, the reaction pressure in the furnace is controlled at 6 kPa, the molar ratio of hydrogen to trichloromethylsilane is 8:1, and the deposition time is 2 hours.

[0103] (9) The introduction of trichloromethylsilane gas was stopped, and then the flow rates of hydrogen and argon were gradually reduced and completely stopped within 5 minutes. The SiC / SiC composite material after the SiC layer was deposited was kept at 1200° C. in a furnace for 0.5 hour.

[0104] (10) The temperature of the deposition furnace was raised to 1250°C, and hydrogen, argon and trichloromethylsilane were introduced into the furnace again. The hydrogen flow rate was 5 L / min, the argon flow rate was 10 L / min, and trichloromethylsilane was introduced into the reaction furnace by bubbling hydrogen in the precursor solution. The molar ratio of hydrogen to trichloromethylsilane was 8:1. The reaction pressure in the furnace was controlled to be 25 kPa, and the first CVD stage was carried out. The deposition time was 15 hours.

[0105] (11) The temperature was adjusted to 1150°C, and hydrogen, argon and trichloromethylsilane were continuously introduced into the furnace. The hydrogen flow rate was 5 L / min, and the argon flow rate was 10 L / min. The molar ratio of hydrogen to trichloromethylsilane was 8:1. The reaction pressure in the furnace was controlled to be 25 kPa, and the second CVD stage was carried out. The deposition time was 10 hours.

[0106] (12) The temperature was adjusted to 1050°C, and hydrogen, argon and trichloromethylsilane were continuously introduced into the furnace. The hydrogen flow rate was 5 L / min, and the argon flow rate was 10 L / min. The molar ratio of hydrogen to trichloromethylsilane was 8:1. The reaction pressure in the furnace was controlled to be 25 kPa, and the third CVD stage was carried out. The deposition time was 8 hours.

[0107] (13) After the deposition is completed, the gas is stopped and the temperature in the furnace is lowered. The average cooling rate is 15°C / h. After the temperature in the furnace drops to room temperature, the sample that has completed CVD is taken out, and the surface of the material is lightly polished to remove surface particles and protrusions to make the surface as smooth as possible. The dust remaining on the surface during the polishing process is removed to obtain a SiC / SiC composite cladding tube.

[0108] Example 3

[0109] A method for preparing a SiC / SiC composite cladding tube comprises the following steps:

[0110] (1) Precursor polycarbosilane (PCS) is dissolved in xylene to prepare a precursor mixed solution, wherein the room temperature viscosity of the SiC precursor solution is 40 mPa·s.

[0111] (2) The SiC / SiC composite material tube is placed in a 316L stainless steel tube for vacuum impregnation, with a tube diameter of 10 cm. Ventilation pipes are provided near both ends of the stainless steel tube for injecting the precursor solution of the impregnated SiC and for vacuuming.

[0112] (3) The SiC precursor solution was injected into the stainless steel pipe through the ventilation pipe, and the SiC precursor solution was completely immersed in the SiC / SiC composite material tube. The ventilation holes at both ends and one end of the stainless steel pipe were sealed to keep it airtight. A mechanical pump and a molecular pump were used to evacuate the other end to make the air pressure in the stainless steel pipe lower than 4×10 -3 Pa, the SiC / SiC composite tube was vacuum impregnated for 8 hours.

[0113] (4) introducing argon gas into the stainless steel pipe to make the SiC precursor mixed solution flow out, and continuing to introduce argon gas into the stainless steel pipe to dry the impregnated SiC / SiC composite material tube, the drying temperature is 1100° C., and the drying time is 1 hour.

[0114] (5) The dried SiC / SiC composite tube is taken out from the stainless steel pipe, placed in a high-temperature cracking furnace, and heated in an argon inert atmosphere at 1300° C. to convert the SiC precursor solution impregnated in the SiC / SiC composite tube into a SiC ceramic matrix. The high-temperature cracking time is 0.5 hours, and the temperature is slowly cooled to room temperature after the high-temperature cracking is completed.

[0115] (6) The SiC / SiC composite material tube is taken out of the high-temperature cracking furnace, and the surface of the SiC / SiC composite material tube is lightly polished to remove surface particles and protrusions to make the surface flat, and the dust remaining on the surface during the polishing process is removed.

[0116] (7) Repeat the vacuum impregnation-curing-cracking process of steps (2) to (6), and perform the vacuum impregnation-curing-cracking process for a total of 3 rounds, the fibers on the surface of the SiC / SiC composite tube are completely covered, and the mass increase rate of the last round of PIP is less than 1%, thereby obtaining a densified SiC / SiC composite intermediate layer.

[0117] (8) The prepared densified SiC / SiC composite material intermediate layer was placed upright in a 900°C chemical vapor deposition furnace for chemical vapor infiltration (CVI). The specific process was as follows: hydrogen, argon and trichloromethylsilane were introduced into the furnace, wherein the flow rate of hydrogen was 1 L / min and the flow rate of argon was 5 L / min; deposition was carried out at 900°C, the reaction pressure in the furnace was controlled at 2 kPa, the molar ratio of hydrogen to trichloromethylsilane was 12:1, and the deposition time was 8 hours.

[0118] (9) The introduction of trichloromethylsilane gas was stopped, and then the flow rates of hydrogen and argon were gradually reduced and completely stopped within 5 minutes. The SiC / SiC composite material after the SiC layer was deposited was kept at 900° C. in a furnace for 3 hours.

[0119] (10) The temperature of the deposition furnace was raised to 1300°C, and hydrogen, argon and trichloromethylsilane were introduced into the furnace again. The hydrogen flow rate was 1 L / min, and the argon flow rate was 5 L / min. Trichloromethylsilane was introduced into the reaction furnace by bubbling hydrogen in the precursor solution. The molar ratio of hydrogen to trichloromethylsilane was 12:1. The reaction pressure in the furnace was controlled to be 15 kPa. The first CVD stage was carried out, and the deposition time was 15 hours.

[0120] (11) The temperature was adjusted to 1250°C, and hydrogen, argon and trichloromethylsilane were continuously introduced into the furnace. The hydrogen flow rate was 1 L / min, and the argon flow rate was 5 L / min. The molar ratio of hydrogen to trichloromethylsilane was 12:1. The reaction pressure in the furnace was controlled to be 15 kPa, and the second CVD stage was carried out. The deposition time was 10 hours.

[0121] (12) The temperature was adjusted to 1150°C, and hydrogen, argon and trichloromethylsilane were continuously introduced into the furnace. The hydrogen flow rate was 1 L / min, and the argon flow rate was 5 L / min. The molar ratio of hydrogen to trichloromethylsilane was 12:1. The reaction pressure in the furnace was controlled to be 15 kPa, and the third CVD stage was carried out. The deposition time was 8 hours.

[0122] (13) The temperature was adjusted to 1000°C, and hydrogen, argon and trichloromethylsilane were continuously introduced into the furnace. The hydrogen flow rate was 1 L / min, and the argon flow rate was 5 L / min. The molar ratio of hydrogen to trichloromethylsilane was 12:1. The reaction pressure in the furnace was controlled to be 15 kPa, and the fourth CVD stage was carried out. The deposition time was 8 hours.

[0123] (14) After the deposition is completed, stop introducing gas and lower the temperature in the furnace. The average cooling rate is 25°C / h. After the temperature in the furnace drops to room temperature, take out the sample that has completed CVD, lightly grind the surface of the material to remove surface particles and protrusions to make the surface as smooth as possible, and remove the dust remaining on the surface during the grinding process. The SiC / SiC composite cladding tube is completed.

[0124] Comparative Example 1

[0125] The preparation method is exactly the same as that of Example 1, except that steps (8) and (9) are omitted, that is, the CVI step is not performed, and the temperature is not adjusted to 1150°C in step (11), and the temperature of step (10) is kept unchanged, that is, the deposition temperature of step (11) is 1250°C.

[0126] The SiC / SiC composite cladding tube of Comparative Example 1 was densified by PIP, without CVI to improve the interface, and CVD coating was deposited at a constant temperature. Figure 4 As shown, CVD obtains a SiC outer coating with a thickness of about 360 microns, and there is a pyrolytic carbon interface layer with a width of microns between the coating and the composite material layer. The thicker pyrolytic carbon interface layer in Comparative Example 1 will reduce thermal conductivity, reduce interlayer bonding strength, easily break, and reduce air tightness, as shown in Table 1.

[0127] Comparative Example 2

[0128] The preparation method is exactly the same as that of Example 1, except that the temperature is not adjusted to 1150°C in step (11), and the temperature of step (10) is kept unchanged, that is, the deposition temperature of step (11) is 1250°C.

[0129] The SiC / SiC composite cladding tube of Comparative Example 2 was densified by PIP, CVI was performed to improve the interface, and CVD coating was deposited at a constant temperature. Figure 5 As shown, there is a pyrolytic carbon interface layer with a width of less than 100 nanometers between the SiC outer coating and the composite material layer. The width of the pyrolytic carbon interface layer is reduced compared with that in Comparative Example 1. The CVI layer improves the interface between the CVI layer and the composite material substrate, and improves the interface between the subsequent CVD coating and the CVI layer. However, the single-layer SiC outer coating in Comparative Example 2 is prone to through-cracks during vacuum or positive pressure airtightness testing, thereby reducing airtightness, as shown in Table 1.

[0130] Table 1 Thermal conductivity and test results of SiC / SiC composite cladding tube

[0131]

[0132] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0133] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A method for preparing a SiC / SiC composite cladding tube, It is characterized in that The following steps are involved: (1) vacuum impregnating a SiC / SiC composite material tube in a SiC precursor solution, and after vacuum impregnation, curing and cracking are performed to obtain a densified SiC / SiC composite material intermediate layer; (2) depositing a SiC layer on the outer surface of the densified SiC / SiC composite material intermediate layer obtained in step (1) by a chemical vapor infiltration process; (3) Depositing a SiC layer on the surface of the SiC layer deposited in step (2) using a chemical vapor deposition process.

2. The method for preparing the SiC / SiC composite cladding tube according to claim 1, It is characterized in that In the step (3), the process of depositing the SiC layer by the chemical vapor deposition process includes at least two chemical vapor deposition stages; And / or, the chemical vapor deposition process of depositing the SiC layer is uninterrupted.

3. The method for preparing the SiC / SiC composite cladding tube according to claim 1, It is characterized in that In the step (3), the process of depositing the SiC layer by the chemical vapor deposition process includes 2-6 chemical vapor deposition stages.

4. The method for preparing the SiC / SiC composite cladding tube according to claim 2 or 3, It is characterized in that In the step (3), the deposition temperature of the first chemical vapor deposition stage of the chemical vapor deposition process for depositing the SiC layer is 1100-1400° C.; and / or, the deposition temperature of each chemical vapor deposition stage is 50 to 150° C. lower than the deposition temperature of the previous chemical vapor deposition stage; And / or, the deposition time of each chemical vapor deposition stage is 5 to 20 hours.

5. The method for preparing the SiC / SiC composite cladding tube according to claim 1, It is characterized in that In the step (3), hydrogen, argon and trichloromethylsilane are introduced into the chemical vapor deposition process; the molar ratio of the hydrogen to trichloromethylsilane is 8 to 12:1; And / or, the pressure of the chemical vapor deposition is 15-25 kPa.

6. The method for preparing the SiC / SiC composite cladding tube according to claim 1, It is characterized in that In the step (1), the preparation of the SiC / SiC composite material tube comprises: weaving SiC fibers into a SiC fiber preform, and then preparing the SiC fiber preform through a SiC matrix to obtain a SiC / SiC composite material tube; the preparation method of the SiC matrix comprises at least one of chemical vapor infiltration, chemical vapor deposition, precursor impregnation pyrolysis, and nano-impregnation transient eutectic; And / or, the SiC precursor solution includes a polymer precursor and a solvent; the polymer precursor includes at least one of polycarbosilane, polymethylsilane, and polyvinylsilane; the solvent includes at least one of xylene, toluene, and trimethylbenzene; And / or, the room temperature viscosity of the SiC precursor solution is 20 to 40 mPa·s; and / or, the vacuum impregnation pressure is less than 5×10 -3 Pa; the vacuum impregnation time is 2 to 15 hours; And / or, the cracking temperature is 1000-1300° C.; the cracking time is 0.5-2 h.

7. The method for preparing the SiC / SiC composite cladding tube according to claim 1, It is characterized in that In the step (1), the vacuum impregnation, curing and cracking process in step (1) is repeated; the vacuum impregnation, curing and cracking process is repeated 2 to 10 times until the surface fibers of the SiC / SiC composite material tube are completely covered by the SiC matrix obtained by impregnation and cracking of the SiC precursor solution, and the mass increase rate of the SiC is less than 1%, and the vacuum impregnation, curing and cracking process is stopped to obtain a densified SiC / SiC composite material intermediate layer.

8. The method for preparing the SiC / SiC composite cladding tube according to claim 1, It is characterized in that In the step (2), hydrogen, argon and trichloromethylsilane are introduced into the chemical vapor infiltration process, and the molar ratio of the hydrogen to trichloromethylsilane is 8 to 12:1; And / or, the deposition temperature is 900-1200° C.; the deposition pressure is 2-6 kPa; the deposition time is 2-8 h; And / or, after the SiC layer is deposited by chemical vapor infiltration process, the introduction of trichloromethylsilane is stopped, and then the temperature is kept at 900-1200° C. for 0.5-3 hours.

9. A SiC / SiC composite cladding tube, It is characterized in that The method is prepared by the method described in any one of claims 1 to 8.

10. Use of a SiC / SiC composite cladding tube obtained by the preparation method described in any one of claims 1 to 8 or a SiC / SiC composite cladding tube described in claim 9, It is characterized in that The SiC / SiC composite material cladding tube is used in a nuclear reactor.

Citation Information

Cited By

  • SiC edge ring and preparation method and application thereof

    CN119530756A